Integration of micro-CT and uniaxial loading to analyse the evolution of 3D microstructure under increasing strain: application to the Anterior Cruciate Ligament. (2019) - Marchiori, G.; Parrilli, A.; Sancisi, N.; Berni, M.; Conconi, M.; Luzi, L.; Cassiolas, G.; Zaffagnini, S.; Lopomo, N.F.
Abstract: Anterior Cruciate Ligament (ACL) is one of the main ligaments within the knee. ACL is a dense fibrous tissue, its nonlinear stress-strain behaviour is related to fibres uncrimping, reorienting and tensioning, which inherently define its functional properties. Aim of this study was to design a setup able to acquire the 3D fibrous microstructure of ACL samples evolving under strain. A specific tensioning device – consisting in two clamps to hold the sample, a linear guide moved by a threaded rod for sample elongation, a load cell to measure reaction force and an aluminum frame – was designed to be inserted into the chamber of a high resolution micro-CT system (Skyscan 1176). Once clamped, ACL underwent 1, 2, 3, 4, 6 and 8% of elongation to reveal toe and linear region of the stress-strain curve. At each specific strain, specimen was scanned with a nominal resolution of 9 μm to non-destructively obtain 3D microstructure. Before testing, collagen fibres were highlighted by an optimized contrasting protocol which included the staining of ACL in a solution of 2% PTA in H2 O. With the specific contrasting procedure and micro-CT resolution, it was possible to show the effect of strain variation on the different fibres bundles. Presented procedure makes it possible to obtain fundamental information about mechanical and microstructural characteristics, simultaneously addressing clinical and engineering issues related to ACL reconstruction. Current work is related to micro-CT image processing, in order to perform a 3D morphometric analysis on the fibres bundle changes in relation to their mechanical behaviour.